The Measurement of Physical Workload and Mental Workload Level of Medical Personnel - Dian Palupi Restuputri; Anindia Karunia Pangesti; Annisa Kesy Garside (Jurnal Teknik Industri, 2019)
As the primary health reference center, a hospital must provide excellent quality services to each patient. The impact of the extreme physical and mental workload causes negligence in activities. It affects the quality of services provided by medical personnel. This study investigated the level of mental workload and physical workload in medical staff in a hospital. This study was conducted at 15 units in the hospital. The mental workload was assessed using the NASA-TLX Questionnaire. The physical workload analysis was carried out with the Heart Rate reserve percentage of medical personnel. This study shows that the mental workload of nurses in the  Intensive Care Unit (ICU) is higher than the other units. Whereas the calculation of physical load using % HR reserve turns out the nurse's head in-unit class 1 has the highest value than the other unit. The statistical analysis showed a difference in the general practitioner workload toward the Head of Nursing.